The determinants of sovereign bond yield spreads in the EMU - António Afonso; Michael G. Arghyrou; Alexandros Kontonikas (European Central Bank (ECB), 2015)
We use a panel of euro area countries to assess the determinants of long-term sovereign bond yield spreads over the period 1999.01-2010.12. We find that, on top of the fundamentals themselves, changes in the sensitivity of bond prices to fundamentals are also necessary to explain yields over the crisis period. We also find that the menu of macro and fiscal risks priced by markets has been significantly enriched since March 2009, including international financial risk and liquidity risk. Finally, we find that sovereign credit ratings are statistically significant in explaining spreads, yet compared to macro- and fiscal fundamentals their role is limited.
Keywords: C23; E62; H50; 330; credit ratings; Government debt; panel analysis; sovereign yields